EVALUATION OF PRINCIPAL MANAGERIAL IMPLEMENTATION - Herlina LIDIAWATI; Hamid AL JUFRI; Abd Rahman A. GHANI (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2022)
This study aims to determine the implementation of the principal at SD Negeri Sukajaya 01 Sukajaya District, Bogor Regency. The method used is the Qualitative Method. The evaluation model used is inequality (DEM). Collecting data obtained from various sources, backgrounds and sources through literature study. The results of this study indicate that the implementation of the Principal in managing the School in Standards of Facilities and Infrastructure and Standards of Educators and Education Personnel needs to be improved. The research subjects are the Principal, and the teachers. The object of research is all that is in the school under study. The research instrument intended as a data collection tool in this study were: grid sheets equipped with interview guidelines, in the form of questions, observations, and documentation studies of all observation activities carried out. Data collection techniques using the method of observation, interviews and documentation studies. Data analysis techniques are planning, data collection, data separator, verification and drawing conclusions. The results of the study show that: 1) the fulfillment of the standard of facilities and infrastructure is not optimal 2) the fulfillment of the standards of educators and education personnel needs to be improved 3) the fulfillment of the standards of sarpras and teaching and educational staff is not in accordance with the duties and functions of the principal. Duties and functions of the Principal as Manager 4) need to analyze the school's obstacles and challenges through a SWOT analysis.